Ethnoparenting Strategies in Baduy: Strengthening Early Childhood Resilience through Scientific Literacy - Sari Gusmawanti; Euis Kurniati; Rita Mariyana (Universitas Pendidikan Ganesha, 2026)
This study is motivated by the urgent need for an early childhood parenting model that not only preserves local cultural values but also fosters contextual science literacy from an early age. The purpose of this research is to analyze ethnoparenting strategies in building children’s life resilience through the integration of cultural values, spirituality, and experiential science literacy principles. This study employs a qualitative approach using ethnographic methods. The research subjects include parents and customary leaders within an indigenous community. Data were collected through participatory observation and in-depth interviews, supported by observation guidelines and interview protocols as research instruments. Data were analyzed using an interactive model consisting of data reduction, data display, and continuous conclusion drawing. The findings reveal that ethnoparenting practices are embedded in daily activities that reflect scientific understanding derived from lived experiences, such as reading natural signs, recognizing star cycles, and applying traditional ecological farming systems. These values are also transmitted through stories, myths, and cultural narratives that shape children into resilient, adaptive individuals with strong cultural and environmental awareness. The conclusion of this study is that ethnoparenting functions as a parenting system that integrates cultural, spiritual, and ecological knowledge, which indirectly develops contextual science literacy in children. The implication of this study is that it can serve as a foundation for developing culturally based early childhood education models that are relevant across various community contexts to strengthen children’s character and scientific literacy for the future generation.